Morphophysiological aspects of young Calotropis procera plants submitted to different shading levels - Ribeiro, João Everthon da Silva; Figueiredo, Francisco Romário Andrade; Coêlho, Ester dos Santos; Albuquerque, Manoel Bandeira de (Scientia Plena, 2019)
The silk flower (Calotropis procera) is a plant found practically in the whole Northeast region of Brazil and can be used for several purposes. However, its morphophysiological characteristics may be influenced by the degree of brightness. This study aimed to evaluate the morphophysiological behavior of silk flower under different shading levels. The experiment was carried out in a greenhouse belonging to the Federal University of Paraíba, Areia, Paraíba, Brazil. The experimental design was completely randomized, with five treatments and eight repetitions. The treatments used were different shading levels: 0 (full sun), 30%, 50%, 70% and 90% of shading. Growth characteristics, morphofunctional attributes, gas exchange and chlorophyll a fluorescence were evaluated. The data were submitted to analysis of variance by the F-test, and in cases of significance, a polynomial regression analysis was performed. The best result for the plant height was found at the shading level of 68.4%. Gas exchange and chlorophyll a fluorescence variables presented higher values in the levels of higher light availability. Silk flower plants grow best under full sun conditions. Shading negatively affects the gas exchange and quantum efficiency of silk flower plants.